Abdullah Saeed's Interpretation of the Verses â€œDeath and Ascensionâ€ of Prophet Isa AS in the Quran - Hasani, Fahmi Subhan (UIN Sunan Gunung Djati Bandung, 2023)
Specifically, issues related to Prophet Isa are discussed in 15 surahs and 93 verses in the Quran. The name of Prophet Isa is mentioned 25 times in the Quran, scattered across fifteen different surahs. Meanwhile, the term â€œAl-Masihâ€ is mentioned 9 times, with a direct discussion of death and crucifixion explained only in one verse, namely QS. An-Nisa verses 157-158. These verses are often interpreted by Muslims as the basis for the belief that Prophet Isa did not die. This view differs theologically from the Christian belief that Jesus was crucified and died to redeem the sins of humanity. The understanding of the Quranic text is further explored through the interpretations of Mufassirin, with the hope of producing the best interpretation from Abdullah Saeed and a more comprehensive understanding of the text. The type of research conducted is literature research, where the researcher focuses on collecting data and information from various sources in the library, including books, journals, manuscripts, notes, historical stories, and documents. Abdullah Saeed acknowledges that the Quran is the revelation of God sent to Muhammad, and he believes that the Quran existing today is the original holy book. However, Saeed also notes concerns about the numerous textual interpretations that tend to stop at literal exploration alone. Through this analysis, Saeed seeks to show the complexity of the meaning of the Quran that cannot be overcome by mere literature exploration. Therefore, in the current era of globalization, he advocates a contextual approach to find the true meaning of the text.